Commercial Building Energy Performance - Room cooling principles and hydronic cooling system temperatures - Dahlberg, Charlotta (My University, 2017)
In commercial buildings, considerable amounts of energy are being used for removal of heat and air borne pollutants. Besides negative environmental impact, high energy use also results in high building operation costs, making improved energy performance interesting for property owners. This thesis aims to map typical cooling demands in a commercial building and explore the possibilities, limitations and basic energy demands associated with different room cooling principles. Another aim is to investigate the possibilities of improving hydronic cooling system energy performance by utilisation of “free” cooling sources, and illustrate how the system temperatures in hydronic cooling systems influence the energy performance. In the thesis, an existing commercial building has been studied. With the building as a base, an energy simulation model was developed using the software IDA ICE. The model was used to perform a parametric study through simulations of alternative room cooling principles. The design software AIACalc was used for the analysis of the hydronic cooling system temperatures and the free cooling possibilities. The results show that the cooling demands in the studied building vary mainly depending on the heat load patterns from the businesses in the building. Furthermore, cooling principles utilising airborne cooling were shown to have a lower energy demand compared to those utilising waterborne cooling. The thermal cooling supply was also concluded to be important for the cooling energy performance when utilising waterborne cooling. Regarding the system temperatures and the free cooling possibilities in the hydronic cooling system, conclusions are that the energy performance of the studied building could benefit from an increased free cooling capacity and that deviating system temperatures impairs the energy performance of the cooling system. Evaluating the possibilities of extended heat recovery is identified as a suitable area for further studies due to the existence of many simultaneous building heating and cooling demands.
Keywords: Building Futures; Energi; Hållbar utveckling; Samhällsbyggnadsteknik; Building Futures; Energy; Sustainable Development; Civil Engineering